SISTEM INFORMASI PELAYANAN POSYANDU MELATI BERBASIS WEB MENGGUNAKAN FRAME WORK CODEIGNTER PADA POSYANDU MELATI DESA - Yuliana, Eka; Rakhim, Basuki; Mansyuri, Umar; Rohman, Ali (LPPM Universitas Bina Bangsa, 2024)
Posyandu (Integrated Health Service Post) is a vital community health facility that provides health services for toddlers and pregnant women. However, the data management and reporting processes often face challenges such as limited access to information and data recording errors. Therefore, this research aims to develop a Web-based Information System for Melati Posyandu Service using the CodeIgniter Framework to enhance the efficiency and accuracy of data management and reporting. During the development phase, system requirements analysis and application architecture design were carried out for the web-based application. The implementation of the system utilized the CodeIgniter Framework as the foundation to produce a faster, more efficient, and reliable application. Proposed features include recording health data for toddlers and pregnant women, immunization schedules, weight measurements, and health reports. The results of this research demonstrate that the Web-based Information System for Melati Posyandu Service can improve efficiency in health data recording and reporting. Users, including Posyandu staff, midwives, and administrators, can easily access and manipulate data in real-time. Additionally, the system enhances the quality of service by providing more accurate and comprehensive health information for toddlers. In conclusion, the implementation of the Web-based Information System for Melati Posyandu Service using the CodeIgniter Framework offers significant benefits in data management and health service delivery at Melati Posyandu in Melandang Village. Suggestions for further development encompass maximizing system utilization, adding additional features, conducting regular maintenance, and ongoing evaluation based on user feedback. With these steps, it is expected that the system will more effectively contribute to improving the quality of health services at Posyandu and support comprehensive community health efforts